Attention Economies - Josef Falkinger (Center for Economic Studies and ifo Institute (CESifo), 2003)
Attracting attention is a basic feature of economic life but no standard economic problem. A new theoretical model is developed which describes the general structure of competition for attention and characterizes equilibria. The exogenous fundamentals of an attention economy are the space of receiving subjects with their attention capacity, and the potential set of competing companies (senders) with their radiation technologies. The endogenous variables explained by the theory are equilibrium audiences (the clients belonging to a company), their signal exposure and attention, and the diversity of senders surviving the contest for attention. Application of the equilibrium analysis to changes in information technologies and globalisation suggests that international integration or range-increasing technical progress may decrease global diversity. Local diversity, perceived by the individual receivers, may increase nonetheless.
Keywords: D50; D80; L10; 330